COMPARING THE ACCURACY OF THE MODERN AND TRADITIONAL CALCULATION METHODS IN THE DETERMINATION OF PRAYER TIMES IN MALAYSIA - Zaki, Nurulhuda Ahmad (Online Journal of Research in Islamic Studies, 2017)
This article analyses and compares the traditional and modern calculation methods in determining the prayer times in Malaysia. Around 1800 A.D., prayer times were determined through the traditional method known as rubu’ mujayyab. However, from the mid-19th century till today, the modern calculation method has replaced the traditional method. The traditional method is no longer used because it applied the general descriptive method which made the calculation slow as it took a longer time to use the rubu’ mujayyab manual to calculate the prayer times. Though there are disadvantages in the traditional calculation method, the method should not be abandoned totally as there is research that doubts the accuracy of the results from the modern calculation method. Therefore, this research will analyse the data of prayer times that was accumulated between January to April 2011 by comparing between the modern and traditional calculation methods. The results showed that the traditional calculation method is more accurate and takes a more careful approach compared to the modern calculation method in the aspects of determining prayer times in Malaysia.